The Effect of Credible Online Review, Brand Equity Dimension, and Customer Satisfaction Towards Bio Beauty Lab's Repurchase Intention - Carin Cyntya; Margaretha Pink Berlianto (LPPM Universitas Terbuka, 2023)
Purpose – This study aimed to analyze the effect of Credible Online Reviews, Brand Equity Dimension, and Customer Satisfaction on the Bio Beauty Lab’s customers’ repurchase intention. Methodology –This is a quantitative study conducted on 229 Bio Beauty Lab customers living in Jabodetabek determined using non-purposive sampling. The data collected from the respondents through questionnaire distribution were analyzed using PLS-SEM. Findings – Credible online reviews positively affect brand awareness and perceived value, but do not impact brand personality, organizational associations, and perceived value. Brand awareness, perceived value, brand personality, organizational associations, and perceived quality positively affect customer satisfaction. Additionally, satisfaction affects the Bio Beauty Lab customers' repurchase intention. Originality – This study provides a newer and deeper understanding of credible online reviews and brand equity by focusing on the importance of customer satisfaction and repurchase intention.